2020
DOI: 10.1103/physrevlett.124.093602
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Acoustomechanics with a Micromagnet

Abstract: We theoretically show how to strongly couple the center-of-mass motion of a micromagnet in a harmonic potential to one of its acoustic phononic modes. The coupling is induced by a combination of an oscillating magnetic field gradient and a static homogeneous magnetic field. The former parametrically couples the center-of-mass motion to a magnonic mode while the latter tunes the magnonic mode in resonance with a given acoustic phononic mode. The magnetic fields can be adjusted to either cool the center-of-mass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 49 publications
0
49
0
Order By: Relevance
“…Our treatment of angular momentum transfer in spinlattice interactions should be useful in the study of a variety of problems. Of particular interest would be the application to the magnetic nanosystems like cantilevers [51][52][53] and nanoparticles in polymer cavities [54] or levitated in traps [22][23][24][25]. It could also be extended to study the role of the phonon spin in transport phenomena like the spin Seebeck effect [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our treatment of angular momentum transfer in spinlattice interactions should be useful in the study of a variety of problems. Of particular interest would be the application to the magnetic nanosystems like cantilevers [51][52][53] and nanoparticles in polymer cavities [54] or levitated in traps [22][23][24][25]. It could also be extended to study the role of the phonon spin in transport phenomena like the spin Seebeck effect [1].…”
Section: Discussionmentioning
confidence: 99%
“…where Γ (1) αβ and Γ (2) αβ are due to one-magnon one-phonon and two-magnon one-phonon processes respectively, follow from inserting the ansätze (30) and (31) for the magnon and phonon distribution functions into the kinetic equations (24) and (25). Explicitly,…”
Section: Appendix C: Linear Response Relaxation Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic levitation can be implemented using diamagnetic [32,33] or superconducting particles [27] in external static fields, or ferromagnetic particles above superconductors [34,35]. Interestingly, these systems have been proposed not only for ultrasensitive force and inertial sensing [34,36], but also to test quantum mechanics in currently inaccessible regimes [4], to enable quantum technologies such as quantum magnetomechanics [27] and acoustomechanics [37] and for ultrasensitive magnetometry [11]. In particular, it has been suggested that a levitated micromagnet can overcome the standard quantum limitations to the resolution per unit volume of a magnetometer [11,38].…”
mentioning
confidence: 99%
“…The combination of high mechanical Q-factor, strong spin-mechanical coupling, and long spin-coherence is key for a range of applications such as magnetometers, accelerometers and gyroscopes [53], where the magnet is the sensor which is read out through the NV-center [4]. Furthermore, it may enable the exploration of new phenomena, including dynamics between a levitated nanomagnet and a single flux vortex [57][58][59], precession of a non-rotating magnet due to its intrinsic spin angular momentum [60], preparation of non-Gaussian quantum states [9], mechanically mediated quantum networks [3,61], detection of dark matter [56], and measuring the magnets internal degrees of freedom [54].…”
mentioning
confidence: 99%